Operation Command Transformation of Synchronized Collaborative Design upon Heterogeneous CAD Systems. Issue 4 (December 2013) - Dou, Wanfeng; Song, Xiaodong
Operation command transformation is one of key technologies of the synchronized collaborative design upon heterogeneous CAD systems and becomes a significant challenge because of the great difference in the modeling operations and underground data structures between different CAD systems. A feasible way is to build a neutral operation to aid the conversion of operations among different CAD systems. A method of constructing neutral modeling command set is proposed based on the general parametric feature modeling technique. The set is built by taking the intersection of operation commands from all commercial CAD systems according to parametric feature modeling operations. In order to accomplish the translation of system modeling command (SMC) between different CAD systems, a representation language of neutral modeling command (NMC) is presented to describe these neutral operation commands. By means of the language the translations of SMC-to-NMC and NMC-to-SMC are presented of operation commands from different CAD systems such as Pro/E, UG, SolidWorks. A prototype of synchronized collaborative design is developed based on two common CAD systems Pro/E and UG with their APIs and VC++. The experiments show that our middleware structure increases greatly the efficiency of the system.